The safety of non-incineration waste disposal devices in four hospitals of Tehran - Farshad, Aliasghar (Maney Publishing, 2014)
BACKGROUND: The safe management of hospital waste is a challenge in many developing countries. OBJECTIVES: The aim of this study was to compare volatile organic compounds (VOCs) emissions and the microbial disinfectant safety in non-incineration waste disposal devices. METHODS: VOC emissions and microbial infections were measured in four non-incineration waste disposal devices including: autoclave with and without a shredder, dry heat system, and hydroclave. Using NIOSH and US EPA-TO14 guidelines, the concentration and potential risk of VOCs in emitted gases from four devices were assessed. ProSpore2 biological indicators were used to assess the microbial analysis of waste residue. RESULTS: There was a significant difference in the type and concentration of VOCs and microbial infection of residues in the four devices. Emissions from the autoclave with a shredder had the highest concentration of benzene, ethyl benzene, xylene, and BTEX, and emissions from the hydroclave had the highest concentration of toluene. The highest level of microbial infection was observed in the residues of the autoclave without a shredder. CONCLUSIONS: There is an increased need for proper regulation and control of non-incinerator devices and for monitoring and proper handling of these devices in developing countries.